Variational monte carlo study of light nucle - Khairul Anwar Mohamad Khazali (Institute of Engineering Mathematics, 2015)
This study embarks on the following objectives a full utilization of the realistic Hamiltonian of Argonne V18 two-nucleon and Urbana IX three -nucleon potentials; construct new improvement of the trial Jastrow wave function in VMC method to describe the properties of light nuclei namely 3H, 4He and 6Li. We hope to obtain an accuracy comparable to other techniques such as GFMC and No Core Shell Model (NCSM) methods.